(untitled) (Research, Society and Development, 2021)
The current Mental Health public policy presents as one of its objectives the investiture in the inclusion of people with mental disorders through work. In this context, a fruitful partnership has been established with Solidarity Economy. The objective of this article is to report the experience arising from an extension project conducted by Federal University of Paraná, presenting potentialities, barriers and the strategies adopted for structuring a solidary enterprise situated in the interface with Mental Health. The experience report was structured from the analysis, based on the hermeneutic-dialectic perspective, of field diary, carried out between August 2018 and July 2019. From the report, it is highlighted: the difficulties and potentialities inherent to networking, assuming the importance of the organic and human construction of different institutional partnerships; several actions to build knowledge on Solidarity Economy; the importance of building relationships with locoregional Solidarity Economy networks; the need of the commitment to guaranteeing the right to work; actions to build popular education in Solidarity Economy; the need to build and use devices that promote territorial health care, underlining the contribution of therapeutic accompaniment. Therefore, the need for public policies that provide both structure and support for the development of solidary enterprises and for community care is also highlighted, in order to guarantee conditions for social inclusion of people with mental disorders through the work.